Efeito da ciclofosfamida sobre o desenvolvimento de germes dentais de molares transplantados para a câmara anterior do olho de camundongos. - Matheus, M. T.; Hetem, S. (My University, 1990)
Mice foetus were killed between 13 and 16 days of the gestational period and their molar tooth germs grafted into the anterior chamber of the eye. The hosts were injected either with 6.25 mg/Kg or with 125 mg/Kg of cyclophosphamide and killed 15 days later. The cyclophosphamide irreversibly, interferes on tooth germ development causing either its total degeneration or an alteration on its morphology forming hypodeveloped tooth germs; its action is directly proportional to the foetus age and to the dose used; it does not induce the formation of osteodentin while some predentin partial cell inclusion may occur.
Effect of cyclophosphamide on the development of tooth germs transplanted to the anterior eye chamber of mice
Keywords: cyclophosphamide; animal; anterior eye chamber; drug effect; female; heterotopic transplantation; male; molar tooth; mouse; pregnancy; tooth development; tooth flora; transplantation; Animal; Anterior Chamber; Cyclophosphamide; English Abstract; Female; Male; Mice; Molar; Odontogenesis; Pregnancy; Tooth Germ; Transplantation, Heterotopic